UK monetary policy in an estimated DSGE model with state-dependent price and wage contracts - Haixia Chen; Vo Phuong Mai Le; David Meenagh; Patrick Minford (Cardiff University, Cardiff Business School, 2023)
Considerable micro-level evidence suggests that price/wage contract durations fluctuate with the state of the economy, particularly inflation; nonetheless, macro-level evidence for this is scarce. We incorporate state-dependent price/wage setting into an open economy DSGE model to investigate the evidence of state-dependence in the UK economy's postwar behaviour. The model is estimated and tested using the Indirect Inference method and is found to fit the dynamic behaviour of key variables very well over a long sample period 1955-2021. In the state-dependent scenario, apart from the direct responses to shocks, monetary policy affects the degree to which the economy is close to the NK world, which in turn indirectly affects the response to these shocks; it also potentially pushes interest rates to the Zero Lower Bound, ZLB. Under the interaction of state-dependence and the ZLB, monetary-fiscal coordination is needed to stabilise the economy, as monetary policy alone cannot achieve economic stability during ZLB scenarios, where it must use bond purchases (Quantitative Easing, QE). Our findings suggest that a coordinated monetary-fiscal policy framework, i.e., an interest rate policy that targets nominal GDP complemented by a ZLB-suppressing fiscal policy, decreases the frequency of economic crises and enhances price/output stability and household welfare compared to the baseline Taylor Rule and QE framework.
Keywords: 330; State-dependence; DSGE; QE; ZLB; Monetary Policy; Nominal GDP Targeting; Fiscal Policy; Indirect Inference